Оценка размера теневой экономики промышленного региона - Половян, А.В. (Економіка промисловості, 2015)
На примере Донецкой области предложен и апробирован научно-методический подход к оценке и прогнозированию объемов теневой экономики региона на среднесроч-ую перспективу. В его основу положен комплекс экономико-математических моделей в зависимости от показателей DoingBusiness, что позволяет обосновывать меры по уменьшению теневой экономики. На прикладі Донецької області запропоновано і апробовано науково-методичний підхід до оцінки і прогнозування обсягів тіньової економіки регіону на середньострокову перспективу. В його основу покладено комплекс економіко-математичних моделей залежно від показників DoingBusiness, що дозволяє обґрунтовувати заходи щодо зменшення тіньової економіки. The paper proposes and approves the scientific and methodical approach that allows evaluating and predicting the volume of the shadow economy in the regions of Ukraine in the medium term. Complex economic and mathematical models of the shadow economy at the regional level, depending on the major factors of Doing Business, which determine its size, put in its basis. This allows justifying policies to reduce the volume of the shadow economy and improve the institutional environment. The following assumptions are the basis of the proposed methodology for assessing the size of the shadow economy in the region. The size of the formal economy of the country is the sum of the formal economy of its regions, and the shadow economy of the country is the amount of shadow economies of the regions (quantitative proof of this hypothesis is given in the paper). It is assumed that each branch has technical and technological, and institutional features that significantly influence potential and actual amount of the shadow economy. Psychological behavior of the population in different regions of the country has less impact on the "shadow" economy than on industry-specific. Thus, the size of the shadow economy in Ukraine's regions is defined by their economic structure, as well as system-wide factors that affect the behavior of economic agents (the reliability of institutions that protect property rights, investors rights, enforcement of contracts, the level of the tax burden, and others). The feature of the proposed approach is that it has developed scientific and methodological basis for the formation of primary information technology transformation from open sources on the functioning of the economy of Ukraine in the field and knowledge of the appropriate volume of the shadow economy. The main stages of this transformation are as follows: collection, processing, analysis and storage of raw data, formation of complex econometric models and their parameterization, performance of computational experiments, and interpretation of the results. The practical implementation of the proposed approach has been carried out on the empirical data of the Donetsk region. Software implementation of scientific and methodological approach has been carried out using Anylogic.